2021
DOI: 10.3920/jiff2021.x001
|View full text |Cite
|
Sign up to set email alerts
|

Insect food in space

Abstract: The question addressed here is how to produce palatable food on long-term space flights and during extended tenancy in space colonies. That will be done in closed ecosystems that must be stable, robust, resilient, and sustainable. In these, because of their size, insects will be an obvious food choice. A number of species have been proposed, their suitability based on characteristics such as their capacity to be reared at high densities, ability to convert organic waste, a short life cycle and a high feed conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a specific application, mealworms are a potential sustainable food source in the human exploration of distant planets and other long-duration human space missions [13] because their rapid growth and rich nutrition enable efficient food production [14]. Jones [15] suggested that the daily consumption of roasted mealworms on a long-duration space mission could reach 14,720 g or 161,920 mealworms, considering that 11 mealworms of medium size have a combined mass of 100 g. The potential use of mealworms as a source of protein in deep-space exploration could therefore alleviate logistical challenges and provide astronauts with a sustainable and locally producible meat source [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a specific application, mealworms are a potential sustainable food source in the human exploration of distant planets and other long-duration human space missions [13] because their rapid growth and rich nutrition enable efficient food production [14]. Jones [15] suggested that the daily consumption of roasted mealworms on a long-duration space mission could reach 14,720 g or 161,920 mealworms, considering that 11 mealworms of medium size have a combined mass of 100 g. The potential use of mealworms as a source of protein in deep-space exploration could therefore alleviate logistical challenges and provide astronauts with a sustainable and locally producible meat source [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a specific application, mealworms are a potential sustainable food source in the human exploration of distant planets and other long-duration human space missions [7] because their rapid growth and rich nutrition enable efficient food production [8]. Jones [9] suggested that the daily consumption of roasted mealworms on a long-duration space mission could reach 14,720 g or 161,920 mealworms, considering that 11 mealworms of medium size have a combined mass of 100 g. The potential use of mealworms as a source of protein in deep-space exploration could therefore alleviate logistical challenges and provide astronauts with a sustainable and locally producible meat source [10].…”
Section: Introductionmentioning
confidence: 99%